Violence sons: Young gangs in postwar context in Huamanga City, Ayacucho 2012 - García Escobar, Jorge (2015)
The occurrence of disasters of diverse type always leaves after negative effects in wide population groups. Disasters socially generated when an armed internal conflict, of eminent political gestation have costs to the country, more than time, materials and money, has his worst expression in the loss of lives and in the impacts in the quality of life of the people who managed to survive the event. Peru is not foreign to this type of realities, during part of the final decades of the XX century a civil war explains in a great part of the national territory and had his origin and worse expression in the region Ayacucho. To think more on the effects post war context in a group of population, the present article treats about the changes generated in the short, medium and long term, the political violence in the childhood and teenagers of Huamanga – Ayacucho. In whom we might name without fear of being wrong as the children of the fratricidal war that I put into mourning to the country during more than thirteen years. The work does emphasis on the phenomenon of the juvenile gangs on Ayacucho as expression perhaps more clear of the violence inherited by the young people of this city